Do Financial Constraints Moderate the Impact of Financing Decisions From Internal-financing Sources on Investment? - Andewi Rokhmawati (Jurnal Keuangan dan Perbankan, 2017)
To prevent investment growth from 2013 to 2015 from decreasing, the Industrial Ministry provided fiscal incentives to stimulate investment-growth. Nevertheless, the investment growth of manufacturing firms still declined. This condition indicated that fiscal stimulus might be ineffective to prevent investment-growth from declining. The decline of investment might be influenced by the increase of firm financial constraints to access a source of long term debts. This study aimed to examine the influence of financial constraints in moderating the effect of financing decisions from internal financing sources on investment. The population of the study was all listed-manufacturing firms in Indonesia from 2013 to 2015. Samples were chosen based on the availability of firms’ financial report covering the period of the study. The study concluded that financial constraints significantly weaken the effect of internal funding decision on investment. Unconstrained firms had a higher beta than constrained firms. Although unconstrained firms had an opportunity to choose their source of funding, they preferred to finance their investment from cash flows because the cost of debts might be much higher than the cost of equity. Hence, to help firms to finance their feasible investment opportunity, the government should not only provide tax incentives but also provide a low-interest loan.DOI: https://doi.org/10.26905/jkdp.v21i3.1357